Assessment of the Diversity of Tomato (Solanum Lycopersicum L.) Accessions in the Nigeria National Gene Bank Using Simple Sequence Repeat (SSR) Markers - Olabisi Olajire; Olusola Oduoye; Zainab Jamaleddine; Olatunde Fajimi; David Coker; Abiodun Sunday; Opeyemi Oluwasanya; Best Anukwu; Abiodun Ogundele; Omowumi Ayekun; Yetunde Amos (Journal of Genetic Resources)
Tomato is one of the most cultivated vegetable crops worldwide, with a global production of over one hundred and thirty million tons. Its multi-purpose uses range from being consumed in various forms, including salads, pastes, sauces, and soups, to its culinary and antioxidant properties. Assessment of variability among genetic materials is essential for maintaining and utilizing genetic resources. A fundamental requirement for the effective use of these genetic materials in breeding and crop improvement is a thorough analysis of the genetic variability and structure of the accessions. This study aims to assess the genetic diversity of tomato accessions in the Nigeria gene bank using Simple Sequence Repeat (SSR) markers. DNA was extracted from fifty tomato accessions using the CTAB protocol. The DNA was quantified using a Nanodrop Spectrophotometer and quality-checked on 1%w/v agarose. High-quality DNA was then used for amplification with five polymorphic SSR markers. The total number of alleles was 23, with a mean of 3.20. The polymorphic information content (PIC) values ranged from 0.35 (ODT4) to 0.50 (ODT1), with a mean value of 0.43, while the gene diversity ranged from 0.45 to 0.57, with a mean value of 0.51. The cluster analysis based on the Unweighted Pair-Group Method using Arithmetic Means (UPGMA) grouped the accessions into two major clusters, each with two subclusters. The first major cluster comprised two subclusters of three and thirty tomato accessions, respectively, while the second major cluster had one and sixteen tomato accessions in its subclusters. The results showed that SSR markers were successfully used to discriminate among the tomato accessions based on the PIC and genetic diversity values, hence promoting their use for future crop improvement and contributing to food security.